1989
DOI: 10.2307/2409377
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Exchange between Bacillus subtilis and Bacillus licheniformis: Variable Hybrid Stability and the Nature of Bacterial Species

Abstract: Experiments employing both broth and soil cultures demonstrated the capacity for bidirectional genetic exchange between the eubacterial species Bacillus subtilis and Bacillus licheniformis. The process was studied using standard laboratory strains and wild isolates of these species. The genetic exchange in soil occurs spontaneously. The interspecific recombination involved markers for antibiotic resistance and for the use of specific carbon sources (API characters). Hybrids frequently had unstable phenotypes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 29 publications
2
28
0
Order By: Relevance
“…Animal groups typically lose the ability to exchange genes entirely by the time their mitochondrial DNA sequences are 3% divergent (Avise, 2000), although some animal subspecies as divergent as 16% can exchange genes in nature (Moritz et al, 1992). Bacteria, in contrast, can undergo homologous recombination with organisms as divergent as 25% in DNA sequence (and possibly more) (Duncan et al, 1989;Roberts and Cohan, 1993;Vulic et al, 1997). There are, nevertheless, some important constraints on bacterial genetic exchange.…”
Section: Genetic Exchange In Prokaryotesmentioning
confidence: 99%
“…Animal groups typically lose the ability to exchange genes entirely by the time their mitochondrial DNA sequences are 3% divergent (Avise, 2000), although some animal subspecies as divergent as 16% can exchange genes in nature (Moritz et al, 1992). Bacteria, in contrast, can undergo homologous recombination with organisms as divergent as 25% in DNA sequence (and possibly more) (Duncan et al, 1989;Roberts and Cohan, 1993;Vulic et al, 1997). There are, nevertheless, some important constraints on bacterial genetic exchange.…”
Section: Genetic Exchange In Prokaryotesmentioning
confidence: 99%
“…Why Are Recombination Rates So Low?-Strains of B. subtilis have been shown to recombine spontaneously and at a high rate in soil microcosms (Duncan et al 1989;Graham and Istock 1978), and nearly all native soil isolates tested thus far are naturally competent, although far less so than laboratory strains, in a liquid transformation system (Cohan et al 1991). It is surprising then that the-rate of recombination within naturally competent bacteria such as B. subtilis and B. mojavensis would be so low.…”
Section: Migration Between Populations-slatkin and Maddisonmentioning
confidence: 99%
“…It is surprising then that the-rate of recombination within naturally competent bacteria such as B. subtilis and B. mojavensis would be so low. Second, the soils used in the microcosm experiments are richer and sustain a higher density than occurs in desert soils where B. subtilis is most common (Duncan et al 1989;Mishustin 1975;Johnson and Cameron 1973); such that recombination may be much more likely in the microcosms tested than in the natural habitat. First, the B. subtilis strains used in previous soil microcosm experiments (e.g., Duncan et al 1989;Graham and Istock 1978) were orders of magnitude more competent than almost all desert isolates (Cohan et al 1991).…”
Section: Migration Between Populations-slatkin and Maddisonmentioning
confidence: 99%
“…The species studied here, B. subtilis and B. licheniformis, are well-known to be transformable based on laboratory studies, and here we will provide evidence of local genetic exchange within each of these species in nature, but little or no exchange between them. Given present information, it impossible to know whether these Bacillus species are unusual among bacteria in their remarkably effective capacity for cell-to-cell exchange of DNA (Graham and Istock 1978, 1979,1981Duncan et al 1989, Dubnau 1990. It is premature to think that all Bacillus species are transformable, and it would be an additional unjustified leap to conclude that all Bacillus species undergo genetic exchange in nature.…”
Section: Background For Bacillus Population Studiesmentioning
confidence: 99%
“…Although the DNA-DNA hybridization results of Seki et al (1975) and Priest (1981) indicated only 7%-15% homology between B. subtilis and B. licheniformis, this still leaves strains assigned to these species closely related relative to most other comparisons among the classically defined species in the genus. Despite such considerable DNA sequence divergence, wild isolates and laboratory strains identified as B. subtilis and B. licheniformis exchanged genes spontaneously in laboratory soil microcosms, though, hybrids were frequently unstable genetically (Duncan et al 1989). Interpretations ofthe analysis ofthe genus by Logan and Berkeley (198 1, 1984) must be accompanied by the caveat that the strains they used are not population samples.…”
Section: Background For Bacillus Population Studiesmentioning
confidence: 99%